2021
DOI: 10.4103/njo.njo_49_20
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy in Sub-Saharan Africa

Abstract: Aim: The aim of the study was to provide an updated review on the prevalence and correlates of diabetic retinopathy (DR) in sub-Saharan Africa (SSA). Materials and Methods: A systematic literature search of Medline, Embase, African Journal Online, Africa-Wide Information databases, and Google Scholar for relevant articles was done using a search strategy with key concepts. Studies published between 2010 and 2020 on the prevalence and correlates of DR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This may be due to variations in clinical definitions of diabetes complications in the studies. Burgess et al 134 and Achigbu et al 135 reported a wide disparity in the prevalence of diabetic retinopathy in the included studies of 7%–62.4%, and 13%–82.6%, respectively. Noubiap et al 136 in a systematic review on the burden of diabetic nephropathy in 2015 reported an overall prevalence of chronic kidney disease in patients with diabetes ranging between 11% and 83.7%.…”
Section: Discussionmentioning
confidence: 97%
“…This may be due to variations in clinical definitions of diabetes complications in the studies. Burgess et al 134 and Achigbu et al 135 reported a wide disparity in the prevalence of diabetic retinopathy in the included studies of 7%–62.4%, and 13%–82.6%, respectively. Noubiap et al 136 in a systematic review on the burden of diabetic nephropathy in 2015 reported an overall prevalence of chronic kidney disease in patients with diabetes ranging between 11% and 83.7%.…”
Section: Discussionmentioning
confidence: 97%
“…According to the International Diabetic Federation's (IDF) 2019 report, it was estimated that around 500 million people are living with diabetes worldwide [3], and predicted to be 693 million by 2045 [4]. The majority occurred in low and middle-income countries (LMICs) [5], and 2.6 million diabetes cases were also reported in Ethiopia by 2017 [4].…”
Section: Introductionmentioning
confidence: 99%